Pethia dikhuensis (Teleostei: Cyprinidae), a new species from Nagaland, Northeast, India - Praveenraj, Jayasimhan; Limaakum; Knight, John Daniel Marcus; Moulitharan, Nallathambi; Imchen, Nungsangtemjen (Zootaxa, 2022)
A new species of Pethia from Nagaland, northeastern India is distinguished from all its congeners in the Ganges-Brahmaputra drainage, Kaladan drainage and the Chindwin- Ayeyarwady drainage by the following combination of characters: lateral line complete with 22–23 pored scales up to tail-fin base, 3rd and 4th lateral line scales with minute humeral spot, a large elliptical to rounded black blotch covering 16th to 18th, or 17th to 19th lateral-line scales; live male specimens with reddish-green body above lateral line and reddish-orange beneath; dorsal, pectoral, pelvic, anal and caudal fins reddish-orange; dorsal fin in both sexes with broad black submargin. Genetic analysis based on the mitochondrial cytochrome oxidase unit I (cox1) suggests that the species is distinct from other known species of Pethia for which data are available.